Alterations in spatial memory and anxiety in the MAM E17 rat model of hippocampal pathology in schizophrenia - Gastambide, Francois (Psychopharmacology (Berl), 2015)
Adult rats exposed to methylazoxymethanol acetate (MAM) at embryonic day 17 (E17) display robust pathological alterations in the hippocampus. However, discrepancies exist in the literature regarding the behavioural effects of this pre-natal manipulation. Therefore, a systematic assessment of MAM E17-induced behavioural alterations was conducted using a battery of dorsal and ventral hippocampus-dependent tests. Compared to saline controls, MAM E17-treated rats displayed deficits in spatial reference memory in both the aversive hidden platform watermaze task and an appetitive Y-maze task. Deficits in the spatial reference memory watermaze task were replicated across three different cohorts and two laboratories. In contrast, there was little, or no, effect on the non-spatial, visible platform watermaze task or an appetitive, non-spatial, visual discrimination task, respectively. MAM rats were also impaired in the spatial novelty preference task which assesses short-term memory, and displayed reduced anxiety levels in the elevated plus maze task. Thus, MAM E17 administration resulted in abnormal spatial information processing and reduced anxiety in a number of hippocampus-dependent behavioural tests, paralleling the effects of dorsal and ventral hippocampal lesions, respectively. These findings corroborate recent pathological and physiological studies, further highlighting the usefulness of MAM E17 as a model of hippocampal dysfunction in at least some aspects of schizophrenia.